2014
DOI: 10.1002/hep.27443
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of untreated hepatocellular carcinoma

Abstract: The prognosis of untreated patients with hepatocellular carcinoma (HCC) is heterogeneous, and survival data were mainly obtained from control arms of randomized studies. Clinical practice data on this topic are urgently needed, so as to help plan studies and counsel patients. We assessed the prognosis of 600 untreated patients with HCC managed by the Italian Liver Cancer Group. Prognosis was evaluated by subdividing patients according to the Barcelona Clinic Liver Cancer (BCLC) classification. We also assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
174
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 210 publications
(179 citation statements)
references
References 33 publications
4
174
1
Order By: Relevance
“…To date, there is no effective treatment for HCC, and the lack of effective diagnostic techniques available, due to the undefined etiology and pathogenesis and high-grade malignancy, contributes to poor patient prognosis (2). Ascertaining the origin and development of liver cancer and identification of novel targets for therapy have been the focus of recent studies regarding HCC (3)(4)(5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…To date, there is no effective treatment for HCC, and the lack of effective diagnostic techniques available, due to the undefined etiology and pathogenesis and high-grade malignancy, contributes to poor patient prognosis (2). Ascertaining the origin and development of liver cancer and identification of novel targets for therapy have been the focus of recent studies regarding HCC (3)(4)(5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…Existing prognostic factors such as serum alpha-fetoprotein (AFP), multinodular tumors, [3] tumor Barcelona-clinic liver cancer (BCLC) stage, [3] and tumor size have been identified in previous studies, their prognostic value warrants more investigation and broader applications. However, they have limitations to some extent in sensitivity and specificity.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, a recent study indicated that overall median survival of untreated patients with HCC is about 9 months [6]. The poor prognosis is thought to be a result of several factors.…”
Section: Literature Reviewmentioning
confidence: 99%